(New) Residential architecture for the (new) middle class from the Peruvian north coast in the 21st century - Romero Alamo, Israel (Universidad de Lima. Carrera de Arquitectura, 2019)
In the past years (21st century), the Peruvian north coast architecture, particularly the residential one, has been establishing an architectural expression of identity showing the idiosyncrasy of the designer (architect), his/her education and the education of his/her educators. It is based on a clearly postmodern stance, which is conventional but has modern intentions and discourses, and generates an own unified language in an area of the country openly reliant on Lima. Studied cases showed that there is a formal supremacy based on a purely visual architecture, concerned on the architectural expression and the predominance of the signifier, but with a strong hidden economic and social meaning.